Effects of Trichloroethylene on p53 and Bcl-2 Expression, Chromosome Loss and Catalase Activity Inhibition in Human - Malinee Pongsavee (Indian Journal of Forensic Medicine & Toxicology, 2021)
Trichloroethylene (TCE) is a common organic solvent that has been widely used in industrial applications.TCE is highly lipophilic and readily absorbed into the circulation following oral, dermal or inhalationexposure. The purpose of this study is to examine the alterations of p53 and Bcl-2 expression, chromosomeloss and catalase activity inhibition after treatment with TCE. Human lymphocytes were cultured withvarious doses of TCE for 24 h. Quantitative RT-PCR (qRT-PCR) technique, chromosome culture techniqueand catalase activity assay were performed in human lymphocyte cultures. The results of Quantitative RTPCR (qRT-PCR) analysis showed up-regulated expression in the experimental groups comparison with thecontrol groups of p53 gene [0.016 mM/L (1.4-fold) and Bcl-2 gene [0.008 mM/L (1.4-fold) and 0.016mM/L (1.6-fold)]. Loss of chromosome 8 and 22 were observed. Catalase activity was reduced whenTCE concentration increased (p<0.05). It is indicated that TCE effects on p53 and Bcl-2 gene expression,chromosome loss and catalase activity inhibition. These effects may lead to the onset of cancer in the future.